Broadening of Diffraction Peak Widths and Temperature Nonuniformity During Flash Experiments. Issue 10 (9th June 2016) - Lebrun, Jean‐Marie; Jha, Shikhar K.; McCormack, Scott J.; Kriven, Waltraud M.; Raj, Rishi
Abstract : Thermal expansion arising from Joule heating produces shifts in the diffraction peaks. The shifts are calibrated against the platinum standard to determine the specimen temperature during in ‐situ experiments at the Advanced Photon Source. Temperature gradients within the specimen cause the peaks to shift differently from different parts of the specimen. If the beam travels through the specimen the diffraction peak would broaden as a result of the nonuniform temperature. We report extensive measurements of peak widths in flash experiments over power dissipation levels that range from 300 to 2500 mW/mm 3 . Peak broadening occurs only above a critical power level. The broadening is transient, occurring only near the spike in power dissipation when the power supply is switched from voltage to current control (Stage II); it is estimated to arise from a nonuniformity of ~100°C within the specimen. The broadening subsides in the ensuing state of steady‐state flash under current control (Stage III).